2010
DOI: 10.1177/1066896910382009
|View full text |Cite
|
Sign up to set email alerts
|

CD34, CD117, and Ki-67 Expression in Phyllodes Tumor of the Breast: An Immunohistochemical Study of 33 Cases

Abstract: Phyllodes tumors (PTs) of the breast are biphasic lesions, comprising an epithelial component set within a neoplastic spindle-celled stroma. These tumors have been classified as benign, borderline, and malignant based on a combination of histological criteria, including stromal cellularity, nuclear pleomorphism, mitotic rate, stromal overgrowth, and margin appearance. The aim of this study was to evaluate the expression of CD34, CD117 (c-kit), and Ki-67 in PT of the breast and attempt to correlate the staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
3
30
1
Order By: Relevance
“…First, we tested the expression of Ki67 and myofibroblast markers, including a-SMA, fibroblast activation protein (FAP), and stromal cell-derived factor-1 (SDF-1), in paraffin-embedded phyllodes tumor samples by IHC. Similar to previous studies (20)(21)(22), the expression of Ki67 increased significantly with phyllodes tumors grade (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
“…First, we tested the expression of Ki67 and myofibroblast markers, including a-SMA, fibroblast activation protein (FAP), and stromal cell-derived factor-1 (SDF-1), in paraffin-embedded phyllodes tumor samples by IHC. Similar to previous studies (20)(21)(22), the expression of Ki67 increased significantly with phyllodes tumors grade (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
“…Although the data on increased stromal cellularity are inconsistent, many studies have found that subepithelial condensation of stromal cells is a common feature of PT and may be the best predictor of PT in core biopsies. 16 Stromal overgrowth, defined as a stromal proliferation without accompanying epithelial elements in at least 1 lowpower field (34), is a feature of PT. However, stromal overgrowth is absent in benign PT.…”
Section: 16mentioning
confidence: 99%
“…Studies have shown that p53, Ki67, CD117, 34,35 EGFR, 36 p16, 37 and VEGF 38 (being the lowest in benign PT and the highest in malignant PT) are associated with histologic grades of PT, but none has been proven to be clinically useful. Among these markers, p53 expression and Ki67 index were reported in some studies 39,40 to be significantly associated with disease-free and overall survivals, but other studies 41,42 found no association with recurrence or clinical behavior.…”
Section: Molecular/genetic Featuresmentioning
confidence: 99%
“…6,7 Several other reports have also shown an association of CD117 protein expression with increasing grade, 11,16 with a few detailing preferential expression of CD117 in the malignant phenotype. 6,7,12,17,18 However, there were also several groups that indicated no association between CD117 expression and tumor grade. 8,9,19 In this study, we observed CD117 expression to be associated with borderline and malignant grade tumors.…”
Section: Discussionmentioning
confidence: 99%